Non-nucleoside inhibitors of Zika virus RNA-dependent RNA polymerase - Gharbi-Ayachi, Aïcha (2020)
Zika virus (ZIKV) remains a potentially significant public health concern because it can cause teratogenic effects, such as microcephaly in newborns and neurological disease, like Guillain-Barré syndrome. Together with efforts to develop a vaccine, the discovery of antiviral molecules is important to control ZIKV infections and to prevent its most severe symptoms. Here, we report the development of small nonnucleoside inhibitors (NNIs) of ZIKV RNA-dependent RNA polymerase (RdRp) activity. These NNIs target an allosteric pocket (N pocket) located next to a putative hinge region between the thumb and the palm subdomains that was originally described for dengue virus (DENV) RdRp. We first tested the activity of DENV RdRp N-pocket inhibitors against ZIKV RdRp, introduced chemical modifications into these molecules, and assessed their potency using both enzymatic and cell-based assays. The most potent compound had a 50% inhibitory concentration value of 7.3 μM and inhibited ZIKV replication in a cell-based assay with a 50% effective concentration value of 24.3 μM. Importantly, we report four high-resolution crystal structures detailing how these NNIs insert into the N pocket of ZIKV RdRp. Our observations point to subtle differences in the size, shape, chemical environment, and hydration of the N pocket from ZIKV RdRp from those of the N pocket from DENV RdRp that are crucial for the design of improved antiviral inhibitors with activity against ZIKV.